BAHASA AKUNTANSI SEBAGAI “DISCOURSE-DRIVEN” DALAM BUDAYA KAPITALISME BARU - Banu Witono (Universitas Muhammadiyah Surakarta, 2016)
It is undeniable that accounting as a science or practice developed at this time considered to be born of the